2016
DOI: 10.1111/cas.13010
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of chemotherapy‐induced peripheral neurotoxicity using a point‐of‐care nerve conduction device

Abstract: Chemotherapy‐induced peripheral neurotoxicity (CIPN) seriously impairs patients’ quality of life cumulatively and dose‐dependently. Because assessment of CIPN usually depends on patients’ subjective evaluation of symptoms, objective and quantitative measures are needed. We evaluated a point‐of‐care nerve conduction device (POCD), previously validated for the assessment of diabetic peripheral neuropathy. Sensory nerve action potential (SNAP) amplitude and sensory nerve conduction velocity (SNCV) of the sural ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…While there are a limited number of studies which have evaluated this device [ 16 18 , 36 , 37 ], one study [ 18 ] showed that this device was a reliable and valid tool for polyneuropathy identification and reported thresholds of ≤6μV for AMP POCD and ≤48m/s for CV POCD in 44 adults with T1D and type 2 diabetes. Comparably, we found that the diagnostic performance and POCD-specific thresholds in older adults with longstanding T1D –despite any age-related changes in nerve conduction–were similar to those reported in younger adults with diabetes, implying that this device can be used as a valid screening test for polyneuropathy across broadly-aged adult populations.…”
Section: Discussionmentioning
confidence: 99%
“…While there are a limited number of studies which have evaluated this device [ 16 18 , 36 , 37 ], one study [ 18 ] showed that this device was a reliable and valid tool for polyneuropathy identification and reported thresholds of ≤6μV for AMP POCD and ≤48m/s for CV POCD in 44 adults with T1D and type 2 diabetes. Comparably, we found that the diagnostic performance and POCD-specific thresholds in older adults with longstanding T1D –despite any age-related changes in nerve conduction–were similar to those reported in younger adults with diabetes, implying that this device can be used as a valid screening test for polyneuropathy across broadly-aged adult populations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have mainly investigated the utility of POCD in relation to symptoms and signs of neuropathy, monofilament testing, and 128‐H z tuning fork tests in subjects with diabetes and in patients with chemotherapy‐induced neuropathy . There have been 2 earlier studies comparing the POCD with conventional NCS in 72 and 44 subjects with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory nerve conduction velocity (SNCV) is used to determine sensory nerves status in all the parameters measured in nerve conduction studies. SNCV accurately reflects the myelin integrity and axon caliber [120]. SNCV is slowed by the demyelination of the sensory nerve fibers.…”
Section: Effects Of Flavonoids On Diabetic Painful Neuropathymentioning
confidence: 98%